Association Between Socio-Affective Symptoms and Glutathione and CD4 and CD8 Lymphocytes in College Students - Balderas-Vazquez, Cecilia Luz; Bernal-Morales, Blandina; Garcia-Montalvo, Eliud Alfredo; Vega, Libia; Herrera-Huerta, Emma Virginia; Rodríguez-Landa, Juan Francisco; Velázquez-Hernández, José Felipe; Xotlanihua-Gervacio, María del Carmen; Valenzuela, Olga Lidia (Frontiers in Psychology, 2022)
Background: The prevalence of anxiety and depression in young students is associated with biosocial factors and scholastic stress. However, few studies have evaluated emotional-affective symptoms that are related to the immune system and antioxidant parameters in young individuals without diagnoses of affective disorders. Aim: This study aims to assess the relationship between emotional-affective symptoms and glutathione concentrations and CD4 and CD8 lymphocyte counts in college students. Methods: College students (n = 177) completed standardized psychometric instruments, including the Perceived Stress Scale, Hamilton Anxiety Scale, Beck Depression Inventory, Familiar Social and Friends Support Scale, and Rosenberg Scale. Blood samples were biochemically analyzed. Analyses of variance were conducted between four groups according to symptom severity. Results: A considerable prevalence of stress, anxiety, and depression symptoms was observed and negatively correlated with self-esteem and socio-familiar support. Perceived stress was sexually dimorphic. Although biochemical parameters were within reference ranges, glutathione, CD4, and CD8 tended to be lower in participants with anxiety and depression symptoms, which may be of predictive value. Conclusion: The relationship between antioxidant/immune parameters and socio-affective scores is latent in undiagnosed college students who might develop affective disorders. The findings suggest that during the initial development of affective disorders, stress management strategies should be implemented to help college students cope with the academic load and monitor negative changes in their physiological state.